2020
DOI: 10.1186/s13063-019-3935-x
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic human umbilical cord-derived mesenchymal stem cells for severe bronchopulmonary dysplasia in children: study protocol for a randomized controlled trial (MSC-BPD trial)

Abstract: Background: Bronchopulmonary dysplasia (BPD) is a complex lung pathological lesion secondary to multiple factors and one of the most common chronic lung diseases. It has a poor prognosis, especially in preterm infants. However, effective therapies for this disease are lacking. Stem-cell therapy is a promising way to improve lung injury and abnormal alveolarization, and the human umbilical cord (hUC) is a good source of mesenchymal stem cells (MSCs), which have demonstrated efficacy in other diseases. We hypoth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…The next Phase II clinical trial (NCT03392467) and follow-up (NCT04003857) for intratracheal instillation of UCMSCs to preterm infants with BPD are ongoing 78 , 79 . Recently, Wu et al 80 reported the first randomized, single-center, open-label, dose-escalation, Phase II trial (NCT03601416) using MSCs intravenously administered in children with severe BPD. In this study, the safety and efficacy of treatment with low- ( n =24, 2.5×10 6 cells/kg) and high-dose ( n =24, 5×10 6 cells/kg) intravenous infusions of allogeneic UCMSCs were compared with those of traditional supportive treatments for BPD.…”
Section: Resultsmentioning
confidence: 99%
“…The next Phase II clinical trial (NCT03392467) and follow-up (NCT04003857) for intratracheal instillation of UCMSCs to preterm infants with BPD are ongoing 78 , 79 . Recently, Wu et al 80 reported the first randomized, single-center, open-label, dose-escalation, Phase II trial (NCT03601416) using MSCs intravenously administered in children with severe BPD. In this study, the safety and efficacy of treatment with low- ( n =24, 2.5×10 6 cells/kg) and high-dose ( n =24, 5×10 6 cells/kg) intravenous infusions of allogeneic UCMSCs were compared with those of traditional supportive treatments for BPD.…”
Section: Resultsmentioning
confidence: 99%
“…Studies show that MSCs therapy is beneficial in the treatment of BPD in rodent models, where it promotes angiogenesis, improve alveolarisation and pulmonary hypertension (25)(26)(27) . Data from clinical trials in prematurely born infants at a risk of BPD and children with severe BPD have demonstrated that the umbilical cord-derived MSCs are beneficial (28)(29)(30) . Moreover, limited clinical data indicate that transplanted stem cells can be neuroprotective, and may decrease inflammatory injury in preterm neonates, neonatal stroke, and cerebral palsy (31) .…”
Section: Therapeutic Application Of Mscs In Paediatric Diseasesmentioning
confidence: 99%
“…Stem cell therapy represents a prospective approach in regenerative medicine for the repair, replacement, and rejuvenation of tissue [ 1 , 2 ]. Mesenchymal stromal cells (MSCs) expanded in vitro have been proposed as potential therapy to treat congenital and acquired lung diseases [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. MSCs are multipotent cells that can differentiate into multiple tissue-forming cell lineages, such as osteoblasts, adipocytes, chondrocytes, tenocytes, and myocytes.…”
Section: Introductionmentioning
confidence: 99%